Regulatory mechanisms of plant rhizobacteria on plants to the adaptation of adverse agroclimatic variables - Verma, Krishan K.; Joshi, Abhishek; Song, Xiu-Peng; Liang, Qiang; Xu, Lin; Huang, Hai-rong; Wu, Kai-Chao; Seth, Chandra Shekhar; Arora, Jaya; Li, Yang-Rui (Frontiers in Plant Science, 2024)
The mutualistic plant rhizobacteria which improve plant development and productivity are known as plant growth-promoting rhizobacteria (PGPR). It is more significant due to their ability to help the plants in different ways.Adverse agroclimatic conditions are a very serious problem for agricultural sustainability globally. It causes variations in plants' physic-biochemical, anatomical, cellular, and omic responses, resulting in substantial losses to agricultural output.The main physiological responses, such as malondialdehyde, membrane stability index, relative leaf water content, photosynthetic leaf gas exchange, chlorophyll fluorescence efficiency of photosystem-II, and photosynthetic pigments are observed in plants during unfavorable environmental conditions. Plant rhizobacteria are one of the more crucial chemical messengers that mediate plant development in response to stressed conditions. The interaction of plant rhizobacteria with essential plant nutrition can enhance the agricultural sustainability of various plant genotypes or cultivars. Rhizobacterial inoculated plants induce biochemical variations